OCA Transplantation Outcomes for Replacing Large Bipolar Defects in the Knee using Novel Techniques. Issue 7 (21st July 2017) - Cook, James L.; Stannard, James P.; Kfuri, Mauricio; Crist, Brett D.; Smith, Matthew Jared
Objectives: Osteochondral allograft (OCA) transplantation can functionally restore large articular cartilage defects in the knee, shoulder, hip and ankle. Studies have reported 10-year survivorship between 71% and 85% and up to 74% survivorship at 15 years. Outcomes after OCA treatment have been good to excellent, even in the athletic population in which 88% of patients returned to sport, including 79% returning to preinjury level of sport. However, OCA transplantations for bipolar defects in the knee have traditionally had less favorable results. With the advent of improved allograft preservation methods and refined surgical techniques, OCA transplantations for bipolar defects in the knee have shown a trend toward better outcomes. Therefore, the objective of this study was to report early functional outcomes associated with OCA transplantations to replace large (>4 cm 2 ) bipolar articular cartilage defects in the knee using novel techniques for graft preservation, enhancing bone ingrowth, and implantation. Methods: With IRB approval, patients were enrolled in a dedicated registry for prospective assessment of outcomes after OCA surgery. Demographic and operative data were collected. Outcomes assessments including VAS pain, VAS level of function, IKDC, SANE and PROMIS Mobility are prospectively collected at 6 months and yearly after surgery. All complications and re-operations are recorded. OCA survival is determined based on maintenance of acceptable levels of pain and function and/or need for revision surgery. Data are compared to pre-operative and/or pre-injury levels using repeated measures analyses with significance set at p<0.05. Results: Large bipolar OCA transplantations were performed in 23 knees: femorotibial (n=19), patellofemoral (n=4). Mean age of patients was 34.6 years. Mean pre-operative pain, function, IKDC, SANE and PROMIS Mobility scores were 4.7, 4.1, 40.8, 40.1 and 42.1, respectively. At 6 months postop (n=17), mean scores improved to 1.3, 6, 56.2, 71.8 and 46.1, respectively. At 1 year (n=11), mean scores further improved to 0.4, 8.4, 76.7, 80.6 and 58.4, respectively (Table). Two (8.7%) meniscotibial grafts failed in the first 6 months after surgery and were successfully revised by a second OCA transplantation, making initial survival 91.3%. Five (21.7%) other patients required minor reoperations for lysis of adhesions to restore range of motion and/or screw removal. All subjects are enrolled in the registry and outcomes assessments are ongoing and will be updated for presentation. Conclusion: Bipolar osteochondral allograft transplantation surgeries for treatment of large (>4 cm 2 ) femorotibial or patellofemoral articular cartilage defects in the knee using novel techniques are associated with significant improvements in levels of pain and function at 1 year after surgery. Table – Summary of Outcomes for Large Bipolar OCA Transplantation in Knees Time Point Pain Function IKDC SANE PROMIS Mobility Pre-Operative 4.7 4.1 40.8 40.1 42.1 6 months 1.3* 6.0 56.2 71.8* 46.1 1 year 0.4* 8.4* 76.7* 80.6* 58.4* * denotes statistically significant (p<0.05) improvement from pre-op